ANALISIS PENGARUH FRAUD PENTAGON TERHADAP KECURANGAN LAPORAN KEUANGAN DI PERUSAHAAN PUBLIK YANG TERDAFTAR DI BEI (Studi Empiris pada Perusahaan Sektor Kesehatan dan Teknologi pada tahun 2019-2021) - Wahyutomo, Satrio; Marsono, Marsono (Diponegoro Journal of Accounting, 2024)
This study aims to examine the influence of the pentagon fraud risk factors developed by Crowe Howart on fraudulent financial reporting in health and technology sector companies listed on the Indonesia Stock Exchange in 2019 to 2021. The pentagon fraud risk factors are proxied by external pressure, supervision ineffectiveness, changes in auditors, changes in directors, and CEO narcissism.The samples in this study include 99 samples which consist of 33 companies during 2019-2021 period. The samples were selected through purposive sampling method. The data type is secondary data using financial and annual report as data sources. They were later collected using documentation method then processed using logistic regression analysis method.The research results show that external pressure variable has a significant positive effect on fraudulent financial reporting, while the supervision ineffectiveness has a significant negative effect on fraudulent financial reporting. Variables such as changes in auditor, changes in directors, and CEO narcissism have no significant effect on fraudulent financial reporting. Also Beneish M-score model detected that 22 out of 99 sample companies were suspected of fraudulent financial reporting